PKM Pelatihan Konseling Sebaya untuk Mahasiswa Jurusan Teknik Informatika dan Komputer - Dwi Rezky Anandari Sulaiman; Sanatang; M Miftach Fakhri; Shabrina Syntha Dewi; Della Fadhilatunisa (Sakura Digital Nusantara, 2023)
The purpose of implementing Peer Counseling Training for students is to provide knowledge and skills on how to conduct peer counseling and to instill an understanding that peer counseling is a form of social support for fellow students. The training method employs structured learning with the stages of preparation, assessment, implementation, and evaluation (3PE). The training activities were attended by 26 student representatives who would subsequently provide support to new students. The outcomes of the training indicate that students are capable of understanding the benefits and stages of implementing peer counseling through the conducted simulations. Evaluation results demonstrate that students comprehend that the execution of peer counseling serves as a form of social support for their fellow students.